Mediasi Penal Dan Pengaruhnya Dalam Penyelesaian Tindak Pidana Ringan - Rahmadhyan, Muhammad (Jurnal sosial dan sains, 2025)
Penal mediation is a form of criminal case settlement outside the conventional criminal justice process by emphasizing a restorative approach, which brings together perpetrators, victims, and the community to reach a fair agreement for all parties. In the context of minor crimes, penal mediation provides an alternative settlement that is faster, more efficient, and oriented towards restoring social relations, compared to the formal and protracted litigation process. This study aims to analyze the effect of the application of penal mediation on the effectiveness of minor criminal case settlement. Through a normative juridical approach and case studies of several court decisions, it is found that penal mediation is able to reduce the burden of cases in the courts, accelerate case resolution, and provide more substantial justice for victims. Nevertheless, its application still faces a number of obstacles, such as the limitations of strict regulations and the lack of uniform understanding of law enforcement officials. Therefore, it is necessary to strengthen regulations and integrated training for law enforcement officers so that penal mediation can be implemented optimally, especially in minor criminal cases.